Maqasid Shariah and Islamic Fintech Research: Trends, Topics and Collaborations - Ahmad, Norashikin; Hanapi, Mohd Shukri; Yasin, Yusma Fariza (Jurnal Ilmiah Peuradeun, 2025)
This study examines how Maqasid Shariah principles influence the evolving discourse on Islamic financial technology (FinTech) at the global level. Based on 397 Scopus-indexed publications from 2019 to 2023, the study employs analytical mapping to explore publication trends, thematic developments, and international collaborations. The findings reveal a surge of scholarly attention between 2019 and 2021, followed by a slight decline, with Malaysia identified as the most active contributor. Six key thematic clusters emerged—covering crowdfunding, blockchain, digital assets, and Islamic banking—indicating a gradual shift of Maqasid Shariah from theoretical discussions to practical applications. Conceptually, Maqasid is framed not only as an ethical compass but as a normative and epistemological foundation that integrates Shariah, economics, and technology. Practically, the study offers insights for policymakers and industry players to align digital finance with justice, transparency, and inclusivity while contributing to broader global agendas such as the SDGs and ESG. Although limited to Scopus data, the study encourages further qualitative and comparative inquiries to deepen understanding of Maqasid implementation and strengthen the development of ethical and sustainable Islamic FinTech ecosystems.